2018
DOI: 10.1159/000495209
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Modifies Hamster Behavior and Expression of Inflammatory Factors following Subchronic Unpredictable Mild Stress

Abstract: Background: Previous studies have pointed to the protective role of genistein against stress adaptations although neuromolecular mechanisms are not yet fully known. With this work, we evaluated the influence of such a phytoestrogen on hamster behavioral and molecular activities following exposure to subchronic unpredictable mild stress. Methods: The motor behaviors of hamsters (n = 28) were analyzed using elevated plus maze (EPM) test, hole board (HB) test, and forced swim test (FST). In addition, neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The species used in all of the animal models were limited to rats and mice: we did not find instances of other rodent species that have been utilized as antidepressant screens ( Kramer et al, 1998 ; Alo et al, 2019 ). Fourteen of the studies used rats ( Matsuzaki et al, 2013 ; Minami et al, 2013 ; Tan et al, 2016 ; Liu C. et al, 2017 ; Song et al, 2017 ; Wang et al, 2017 ; Huang et al, 2020 ; Nascimento et al, 2020 ; Lin et al, 2021a ; Zhang L. et al, 2021 ; Lin et al, 2021b ; Anuar et al, 2022 ; Cheng, 2023 ; Rakoczy et al, 2023 ), while the remaining 36 studies used mice to test for antidepressant-like effects ( Zhou et al, 2005 ; Nishizawa et al, 2007 ; Koo et al, 2008 ; Singh et al, 2014 ; Tianzhu et al, 2014 ; Socala et al, 2015 ; Yao et al, 2015 ; Gupta et al, 2016 ; Huang et al, 2016 ; Nakamichi et al, 2016 ; Song et al, 2016 ; Xu, 2016 ; Bao et al, 2017 ; Liu Y. et al, 2017 ; Lin et al, 2017 ; Chiu et al, 2018 ; Mahmoudi et al, 2018 ; Ryu et al, 2018 ; Jin et al, 2019 ; Li et al, 2019 ; Song et al, 2020 ; Li H. et al, 2021 ; Li TJ.…”
Section: Resultsmentioning
confidence: 99%
“…The species used in all of the animal models were limited to rats and mice: we did not find instances of other rodent species that have been utilized as antidepressant screens ( Kramer et al, 1998 ; Alo et al, 2019 ). Fourteen of the studies used rats ( Matsuzaki et al, 2013 ; Minami et al, 2013 ; Tan et al, 2016 ; Liu C. et al, 2017 ; Song et al, 2017 ; Wang et al, 2017 ; Huang et al, 2020 ; Nascimento et al, 2020 ; Lin et al, 2021a ; Zhang L. et al, 2021 ; Lin et al, 2021b ; Anuar et al, 2022 ; Cheng, 2023 ; Rakoczy et al, 2023 ), while the remaining 36 studies used mice to test for antidepressant-like effects ( Zhou et al, 2005 ; Nishizawa et al, 2007 ; Koo et al, 2008 ; Singh et al, 2014 ; Tianzhu et al, 2014 ; Socala et al, 2015 ; Yao et al, 2015 ; Gupta et al, 2016 ; Huang et al, 2016 ; Nakamichi et al, 2016 ; Song et al, 2016 ; Xu, 2016 ; Bao et al, 2017 ; Liu Y. et al, 2017 ; Lin et al, 2017 ; Chiu et al, 2018 ; Mahmoudi et al, 2018 ; Ryu et al, 2018 ; Jin et al, 2019 ; Li et al, 2019 ; Song et al, 2020 ; Li H. et al, 2021 ; Li TJ.…”
Section: Resultsmentioning
confidence: 99%
“…In another experimental study by Alò et al, the anxiolytic and antidepressant effects of genistein were reported. In this study, it was observed that that genistein up‐regulates Hsp70 and TrkB mRNAs in the hippocampus and hypothalamus and reduced the NF‐kB1 levels (Alò et al., 2019). In addition, Atteritano et al, in a randomized trial study showed that the daily administration of genistein at a dosage of 54 mg for 2 years improved the quality of life and depression symptoms in osteopenic postmenopausal women (Atteritano et al., 2014).…”
Section: Therapeutic Effects Of Genisteinmentioning
confidence: 88%
“…In order to evaluate the argyrophilic reaction, an ACS staining technique was used to determine cerebellar fields that featured advanced damaged cell bodies, dendrites, axons, and terminals of both HFD and DZ treated groups subjected to a diet for 16 consecutive weeks. For this part, cerebral sections (30 µm) were obtained from each of the above experimental groups: CTRL ( n = 4), HFD ( n = 4) and HFD ± DZ ( n = 4), at an interval of 240 µm for ACS procedures as previously described [ 28 ]. The estimation of damaged limbic neuronal fields required the volume (defined as Vref) of three layers of cerebellar cortex, and namely the molecular layer (ML), Purkinje layer (PL), and granular layer (GL) by using the following formula: …”
Section: Methodsmentioning
confidence: 99%